Invisible villages: changing residential patterns and relationships in a rural village - Robinson,Helen (Social Anthropology, 2016)
This study centres on the village of Greyton, near Caledon in the Western Cape. It investigates the contemporary and historic changes in its population, residence patterns, relationships and economic activity. It focusses particularly on the effects of the implementation of the Group Areas Act in the village in 1969 and the change from an apparently integrated agricultural settlement to a highly differentiated holiday and retirement resort. This thesis questions the validity of the term "community" within the constraints and contradictions imposed by the establishment of Group Areas. It examines the idea of visible and invisible villagers in the context of separate development and, in the light of the changes which have taken place, it considers the relative importance of a progressive attitude in social and economic planning as opposed to a policy of preservation of the original character of a rural village.